The Analysis Using Semiotic Theory on Teh Pucuk Harum Advertisement - Kadek Agus Mahardika Yasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
In this study, it is aiming to analyze an advertisement which will lead to how advertisers communicate with potential consumers and how producers make good and friendly advertisements with everyone. Data analysis of this study uses a semiotic approach with the theory of Ferdinand De Saussure and Roland Barthes. In Saussure's theory, the study is carried out on the sign in the object, namely the signifier and also the signified. The signifier here according to Saussure is something that is physical, can be felt, such as images, movements or sounds. Usually in the advertisement section, which includes the signifier section according to Saussure's theory, is the photo of the advertisement or the movement of the sign in the advertisement. The signified part is a meaning or value contained in a subject or in other words the signified is a description of a signifier. Then the next theory is from Barthes, the theory put forward by Roland Barthes examines three things, namely denotative, connotative, and mythical meanings in an advertisement based on movement and also the signs in an advertisement. The results of the analysis on the